(untitled) (Research, Society and Development, 2020)
Chronic hemodialysis patients have a nutritional deficit and an inflammatory state that contribute exponentially to the morbidity and mortality of these patients. From then on, the objective was to evaluate the effects of supplementation with flaxseed oil on the nutritional and inflammatory status of patients on chronic hemodialysis in the city of Patos, Paraíba. The research is a prospective longitudinal study, of an interventional clinical type, involving 28 adult patients of both genders undergoing chronic hemodialysis. The patients were randomly divided into two groups: Control Group (CG) and Experimental Group (GE), received mineral oil and flaxseed oil, respectively, both in the proportion of 5 mL daily for the period of 60 days. Anthropometric and biochemical data were collected. The results obtained showed that the values of lymphocytes, monocytes as well as potassium, ferritin, tranferrine, creatinine, previously increased, after supplementation with linseed oil, reached the values considered normal, for women. It is suggested an evaluation in larger quantities and for a longer time to evaluate results.